2001
DOI: 10.1067/mva.2001.119891
|View full text |Cite
|
Sign up to set email alerts
|

Tibia fracture after fibula resection for distal peroneal bypass

Abstract: The lateral approach to the distal peroneal artery has been used by vascular surgeons for 25 years. No complications specifically related to this approach have previously been reported. We reviewed 18 cases of peroneal bypass for limb salvage using the lateral approach with fibula resection and found that two of these cases had ipsilateral tibia fractures within 1 year of the bypass. Eight out of 18 cases were women, and two of these eight had tibia fracture. Both women suffered from osteoporosis. We conclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…17 On the other hand, our patency and LS rates correlate well with the only previouslypublished study dealing with the terminal PA being used in primary or secondary distal revascularizations for CLI because a more proximal outflow vessel was unavailable: 23 in a series of 159 revascularizations performed in 143 patients during a 14-year period, Darling et al 23 reported 1-and 5-year SP rates of 86% and 75%, respectively, with a 5-year LS rate of 87%, demonstrating that these reconstruction procedures achieved much the same hemodynamic results as PT or DP, and PB bypass grafts. Revascularizations to the distal third of the PA were also found as reliable in effecting LS as the proximal two thirds of the PA or other perimalleolar arteries in the same investigators' hands, 1,5,8,10 and their results were comparable with those obtained by many authors advocating the use of PA bypass procedures for LS, though none of them specifically focused on the terminal PA. [2][3][4]6,7,9 In our study, the mean time to wound healing and the proportion of wounds completely healed during the follow-up were similar after distal PA or inframalleolar and PBs bypasses, despite a significantly higher incidence of 26 we found that the lateral approach to the PA provides excellent exposure of the PA distal tract, and, in our opinion, it is quicker and easier than the medial approach.…”
Section: Discussionsupporting
confidence: 49%
“…17 On the other hand, our patency and LS rates correlate well with the only previouslypublished study dealing with the terminal PA being used in primary or secondary distal revascularizations for CLI because a more proximal outflow vessel was unavailable: 23 in a series of 159 revascularizations performed in 143 patients during a 14-year period, Darling et al 23 reported 1-and 5-year SP rates of 86% and 75%, respectively, with a 5-year LS rate of 87%, demonstrating that these reconstruction procedures achieved much the same hemodynamic results as PT or DP, and PB bypass grafts. Revascularizations to the distal third of the PA were also found as reliable in effecting LS as the proximal two thirds of the PA or other perimalleolar arteries in the same investigators' hands, 1,5,8,10 and their results were comparable with those obtained by many authors advocating the use of PA bypass procedures for LS, though none of them specifically focused on the terminal PA. [2][3][4]6,7,9 In our study, the mean time to wound healing and the proportion of wounds completely healed during the follow-up were similar after distal PA or inframalleolar and PBs bypasses, despite a significantly higher incidence of 26 we found that the lateral approach to the PA provides excellent exposure of the PA distal tract, and, in our opinion, it is quicker and easier than the medial approach.…”
Section: Discussionsupporting
confidence: 49%
“…Thus, when the fibula is removed and the torsion stiffness of the construct becomes reduced, a larger twist on the tibia for a given torque can be implied. Previous studies that reported tibia fracture following fibula resection (Emery et al, 1996;Kahn et al, 2001) indicated mainly nonspiral fractures at the level of the fibula resection. It is quite unlikely therefore that these fractures were due to torsional effects, as then the fractures would be typically spiral.…”
Section: Discussionmentioning
confidence: 98%
“…Although it is the most commonly used approach for distal access of the peroneal artery, lateral access with partial fibular resection can increase stress on the tibia and, as previously demonstrated, could predispose patients to tibial fracture, especially older women with osteoporosis. 9 …”
Section: Discussionmentioning
confidence: 99%